Hubungan Antara Motivasi Kerja Dengan Disiplin Kerja Karyawan PT Harmoni Panca Utama Site BDA - Putriyady Putriyady; Ceria Hermina; Lita Ariani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Quality human resources are the result of good work motivation and work discipline. Good work discipline is the result of behavior carried out with awareness and a sense of willingness to comply with all regulations. The aim of this research is to determine the relationship between work motivation and work discipline in companies. The type of research used is quantitative research with a correlational approach. This data collection method uses a scale of work motivation and work discipline. The data analysis method used in this research is in accordance with Karl Pearson's Product Moment correlation technique and uses the SPSS 25.0 application. The results of the product moment correlation calculation obtained a value of 0.756, meaning there is a positive relationship between work motivation and work discipline.